PENGARUH OPTIMALISASI PEMANFAATAN ASET TETAP MILIK PEMERINTAH DAERAH DALAM MENINGKATKAN PENERIMAAN RETRIBUSI DAERAH DI KOTA KUPANG - Frederika Rambu Pekuwali; Thobias E. D. Tomasowa; Jandri P. Z. Ratukadja (JAKA - Jurnal Jurusan Akuntasi, 2020)
This study aims to determine the effect of optimizing the use of fixed assets owned by local governments in increasing local retribution receipts in Kupang City. The purpose of this study was to determine the effect of optimizing the use of fixed assets belonging to the region in increasing the local retribution revenue in Kupang City. The research method used to determine the extent to which optimization of the management of fixed assets (land) belonging to the region in increasing the revenue of the Regional Retribution in Kupang City. Data analysis in this study used descriptive analysis and quantitative analysis with simple linear regression models and statistical tests using SPSS 20 software. in Kupang city not all utilization methods are implemented. The utilization method used is only rent, cooperation in the use and build-up to deliver and there is a significant relationship between the use of assets and the receipt of local user fees, which means that if the utilization of land assets increases, the revenue from local fees will also increase even though it has a very small contribution